L’antimelodramma di Victor Hugo: la vendetta di Triboulet (Materiali di Estetica. Terza serie, 2017)
The purpose of the essay is to demonstrate through the analysis of Hugo’s Le roi s’amuse how the reconciliation of opposites, which is a typical melodramatic element, is alien to the author’s poetics. In fact, the opposition of contrasts, which turns evil into good in a gradual process of formation, is not revealed in Hugo’s work as a principle of disintegration but, paradoxically, is resolved in an element of harmonious relatedness within a upper unity assured from the function of art.